Parents, Children and Family Relationship Centres: What's Working? - Brown, T.; Campbell, Alan (Australian Academic Press, 2013)
This article reports on a study of parents’ and children's responses to the service they received at two Family Relationship Centres (FRCs) in Perth, Western Australia. Family members who had attended either the Mandurah or Joondalup FRCs sponsored by AnglicareWA between 2010 and 2012 were invited to complete a survey that asked them for their views on the services they had received. A total of 74 parents, representing 139 children, completed the survey. Findings indicated significant satisfaction with the two-hour group session that introduces the work of the FRCs, with parents reporting they could remember the main messages from the session. A surprising finding, and one that has not been reported elsewhere, is that parents expressed an unwillingness to invite their own children to participate in the work of the Centres, although the majority of the respondents agreed in principle that children should take part. The implications of this finding are briefly discussed.